2023
DOI: 10.1093/jacamr/dlad038
|View full text |Cite
|
Sign up to set email alerts
|

High incidence of carbapenemase-producingPseudomonas aeruginosaclinical isolates from Lagos, Nigeria

Abstract: Background Carbapenem-resistant Pseudomonas aeruginosa strains are on the rise worldwide. This study characterized clinical isolates of P. aeruginosa from three Nigerian hospitals for carbapenem resistance. Methods Strains isolated from wounds (n = 88), urine/catheter tips (n = 25), sputum/tracheotomy aspirates (n = 5), ear swabs (n = 4) and vaginal swabs (n = 1) were identified by MALDI-TOF and antibiotic susceptibility test… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 66 publications
0
4
0
Order By: Relevance
“…The ICE specifically carrying the aac C3, bla NDM-1 and rmt B4 genes was first reported in the P. aeruginosa isolate “ST773” in the USA in 2019, which was obtained from a returning traveller that underwent surgery in India [ 59 ]. The ICE with the same genetic structure, composition and direct repeat sequences, designated as ICE 6660-like , was also recently found in South Korea [ 55 ], Nepal [ 52 ], Saudi Arabia [ 54 ] and Nigeria [ 53 ]. The international distribution of the bla NDM-1 -positive ST773 clade carrying ARGs on the genetic platforms such as ICEs warrants special attention since ICEs are self-transmissible and can facilitate intra- and intercellular mobility of ARGs [ 60 , 61 ] to other carbapenem-susceptible P. aeruginosa isolates and other Gram-negative bacteria ( Enterobacterales ) in the same region and other countries by travelling, which may further increase the health burden caused by MDR and XDR P. aeruginosa infections.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…The ICE specifically carrying the aac C3, bla NDM-1 and rmt B4 genes was first reported in the P. aeruginosa isolate “ST773” in the USA in 2019, which was obtained from a returning traveller that underwent surgery in India [ 59 ]. The ICE with the same genetic structure, composition and direct repeat sequences, designated as ICE 6660-like , was also recently found in South Korea [ 55 ], Nepal [ 52 ], Saudi Arabia [ 54 ] and Nigeria [ 53 ]. The international distribution of the bla NDM-1 -positive ST773 clade carrying ARGs on the genetic platforms such as ICEs warrants special attention since ICEs are self-transmissible and can facilitate intra- and intercellular mobility of ARGs [ 60 , 61 ] to other carbapenem-susceptible P. aeruginosa isolates and other Gram-negative bacteria ( Enterobacterales ) in the same region and other countries by travelling, which may further increase the health burden caused by MDR and XDR P. aeruginosa infections.…”
Section: Discussionmentioning
confidence: 84%
“…ST773 is an international high-risk clone associated with MDR and XDR phenotypes that produce MBLs (VIMs, IMPs, NDMs), which is widely distributed in countries like Hungary [ 50 ], India [ 51 ], Nepal [ 52 ], Nigeria [ 53 ], Saudi Arabia [ 54 ], South Korea [ 55 ], the UK [ 56 ] and the USA [ 57 ]. The core SNP-based phylogenetic analysis of the study isolates with 19 global ST773 isolates revealed that the study isolates and the eight bla NDM-1 -positive ST773 isolates belonged to the same clade.…”
Section: Discussionmentioning
confidence: 99%
“…This variability might be attributed to lower sample size in such studies. On the other hand, global data showed that CRPA prevalence variations based on different geographic locations such as European and Mediterranean countries (ranging from 10.9% in Sweden to 70.5% in Poland) [20], China (89.4%) [12], Egypt (64.2%) [73], Turkey (20%) [74], India (33%) [75] and Nigeria (40%) [76]. Similarly, a multicenter study in 10 different countries reported 22% [77] and the SENTRY surveillance program 23.9% [78].…”
Section: Discussionmentioning
confidence: 99%
“…Pseudomonas aeruginosa (Pa) is a major human pathogen, responsible for extensive mortality (1), and billions of dollars in health care costs (2,3). Managing Pa infections presents a significant challenge due to its resistance to numerous antibiotics (4) including antibiotics of last resort (5)(6)(7)(8) . Multidrug-resistant (MDR) Pa is recognized as a serious threat by the Centers for Disease Control and Prevention (CDC) and the World Health Organization (WHO), but there are few antibiotics in the clinical pipeline (9,10).…”
Section: Introductionmentioning
confidence: 99%
“…Pseudomonas aeruginosa (Pa) is the most prevalent Gram-negative bacterium associated with wound infections, implicated in 25-50% of all chronic wounds [8][9][10][11] . Managing Pa infections presents a significant challenge due to its chromosomally encoded resistance mechanisms 12 , leading to resistance against numerous antibiotics, including those considered as last-resort options [13][14][15][16] . Multidrug-resistant (MDR) Pa is recognized as a serious threat by the Centers for Disease Control and Prevention (CDC) and the World Health Organization (WHO) 17,18 , but there are few antipseudomonal antibiotics in the clinical pipeline.…”
Section: Introductionmentioning
confidence: 99%